EXPERIENCE OF TREATMENT OF COMORBID PATHOLOGY OF BRONCHOPULMONARY AND CARDIOVASCULAR SYSTEM - Моісєєва, Н.В.; Вахненко, А.В.; М. О. Рум’янцева (World of Medicine and Biology, 2015)
During recent decades have seen a dramatic increase of the number of patients with COPD. This pathology is becoming more substantial medical and social and economic values, and remains one of the major causes of morbidity and mortality worldwide. This is due to environmental pollution, especially air, smoking prevalence and population aging in all countries of the world. Distribution of underdiagnosis of COPD, inadequate antimicrobial therapy lead to increased incidence of complications of COPD and bronchoectasis. Among disadvantages focuses tobacco epidemic, which serves as a common risk factor for the development of not only diseases of the pulmonary system, and cardiovascular system. Significant relevance has polymorbidity, which is particularly characteristic of the older age groups. It is in the group of patients older than 40 years against the background of COPD, there is the rapid progress of CHD, which is one of the leading places in the structure of morbidity and mortality in Ukraine. In view of the high prevalence of CHD and a high probability of serious complications that cause disability and high fatality this problem, except medical, and pronounced social character. It is not difficult to suggest that during exacerbation of bronchoectasis complicated, against CHD requires a more balanced prescribing. And the question of conservative treatment of comorbid disease in the literature is given very few attention. That is why objective of this study was to identify ways to optimize the treatment of moderate-to-severe COPD exacerbations of bronchoectasis complicated for CHD. Previously found that the development and progression of COPD is accompanied by inhibition of the local immune defense system of the bronchial tree and impaired immunity. Among the major disorders of T-cell immunity in patients with COPD complicated bronchoectasis, against CHD can be isolated T-cell immunodeficiencies with predominantly T-helper or T-suppressor of immune deficiency. Identified types of immunological disorders is the basis for immunological correction Glutoxim which has immunomodulatory, bronchodilator, desensitizing, anti-inflammatory and antimicrobial action and is imunorehabilitator. The use of this drug was effective and improved immunological parameters in patients with impaired multivector cellular immunity. According to modern concepts, one of the leading roles in the onset and progression of cardiovascular disease, vascular endothelial dysfunction plays. Therefore, the decrease damage, correction and maintenance of an adequate functioning of the endothelium is one of the most urgent problems of modern therapy of vascular disease especially coronary heart disease. Therefore complement the standard combination therapy Glutoxim and L-arginine aspartate having detoxification activity, membrane stabilizing, antihypoxia, cytoprotective, anti-radical and anti-oxidant action and normalizes the function of the vascular endothelium, led not only to improved immune defense of the body, but also significantly improved the quality of all the parameters of life of patients. Improvement in these areas is beneficial not only to the quality of life of patients, but also for the establishment of compliance. Long-term monitoring of these patients showed a decrease in the number of exacerbations, possibly associated with improved stress tolerance of patients.